Next-generation tour guide – an AR travel assistant - Rao, Yuchen (Nanyang Technological University, 2022)
This project was undertaken to design and develop a mobile application that utilises modern technologies (e.g., augmented reality, machine learning, etc.), aiming to enhance the current travel experience and articulate the vision of a modern travel experience. The app is called “Travelee”. It is designed to be a personal travel assistant to help travellers explore local highlights and discover interesting places around. Due to the time and labour constraints of the project, the design of functions and data are targeted at clients in Singapore, including travellers who are new to Singapore and those looking to rediscover Singapore's hidden gems. “Travelee” was developed using the Flutter SDK and currently supports Android devices compatible with Google AR Service. The first version, which has been developed so far, has three key features: live view AR experience, landmark detection and place recommendation. In addition, the app provides several useful services to make travel more convenient and enjoyable. The report will cover the specifics of the design and development process, as well as product outcomes and potential future iterations. Furthermore, some of the takeaways and reflections are summarised in the final chapter.